Toxicology testing standards: good laboratory practices and the institutional animal care committee - Thomas, Peter (Henry Stewart Talks, 2009)
The patent medicine era and the early role that toxicology played in drug and chemical safety, Dr. Harvey Wiley, his "Poison Squad" and the Pure Food and Drugs Act that lead to the founding of the FDA in the 20th century, Thalidomide, scientific fraud and the promulgation of the Good Laboratory Practices regulations, Outrage over Upton Sinclair's book "The Jungle", the Animal Welfare Act and how this lead to the formation of Institutional Animal Care and Use Committees (IACUC), How study protocols are developed and GLP studies conducted with IACUC input and oversight